Accounting Network Disclosures, Market Competition, and the Implementation of Strategic Management Accounting Technique - Nova Novita; Muhammad Hafidz (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
Strategic Management Accounting (SMA) assists companies in expressing strategic goals and identifying strategies owned by competitors. This study aims to determine whether accounting networking and market competition affect strategic management accounting techniques. This study used a purposive sampling method with 25 samples of the subsector of metal and food and beverage companies in the 2016-2021 observation period. The dependent variable uses the disclosure of thirteen strategic management accounting techniques in the annual report. The market competition variable is measured by market share and the accounting networking, which is measured by the number of board of directors’ companies that have attended training or seminars related to high school technical development. The result found that accounting networking and market competition did not affect the number of strategic management accounting techniques used in the sample companies. These results indicate that even though executives know the benefits of various strategic management accounting techniques, implementing them in companies takes work. This result also discovered that the sample companies used more strategic management accounting techniques that helped increase company efficiency.